BENTUK PENYAJIAN TARI REJANG RENTENG PADA PIODALAN DI PURA PADMASANA DESA LABONU KECAMATAN BASIDONDO KABUPATEN TOLITOLI - Ni Komang Vica Sari; Trubus Semiaji; Riana Diah Sitharesmi; Rahmawati Ohi; Nurlia Djafar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Rejang Renteng Dance is a sacred dance performed by married women and is prohibited for children or unmarried women. Rejang Renteng is performed during the Piodalan ceremony at Pura Padmasana, Labonu Village, symbolizing a dance to guide the deities descending to Earth. This research aims to explain the presentation form of the Rejang Renteng Dance and the changes that have occurred in its presentation, which in turn influence the perfection of the Piodalan ceremony at Pura Padmasana, Labonu Village. This is particularly relevant because the Rejang Renteng Dance at Pura Padmasana Labonu Village shows slight variations in its textual aspects. The research employs a qualitative method. Data collection techniques include observation, interviews, and direct documentation of the dance presentation through videos, photographs, and recordings. The results indicate that the presentation form of the Rejang Renteng Dance at the Piodalan in Pura Padmasana, Labonu Village, can be observed through several aspects: the dance movements consist of three types of movements; the floor patterns consist of two types of patterns; the dancer’s makeup is simple, wearing white kebaya blouses and yellow kamen (traditional clothes). The property used is a yellow sash, and the accompanying music is Gong Kebyar. The number of dancers totals 14. The performance venue is located in the Jaba Mandala area of the temple.